2016
DOI: 10.7448/ias.19.1.20903
|View full text |Cite
|
Sign up to set email alerts
|

Retention in care outcomes for HIV pre‐exposure prophylaxis implementation programmes among men who have sex with men in three US cities

Abstract: IntroductionDespite the efficacy of pre-exposure prophylaxis (PrEP) in preventing HIV transmission, few studies have evaluated PrEP use and retention in care outcomes in real-world settings outside of clinical trials.MethodsData were collected from PrEP clinical care programmes in three mid-size US cities: Providence, Rhode Island (RI); Jackson, Mississippi (MS); and St. Louis, Missouri (MO). We assessed the demographic and social characteristics of patients prescribed PrEP and documented their insurance and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
173
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(194 citation statements)
references
References 28 publications
18
173
3
Order By: Relevance
“…In a three site study in real-world clinical settings, 57% (98/171) of patients were retained in PrEP care at six months. 3 These findings were consistent across three diverse clinical settings in Jackson, Mississippi (61%; 37/61); Providence, Rhode Island (53%; 42/80); and Saint Louis, Missouri (63%; 19/30, p =0.51). However, our higher rates of retention in care reflect our efforts to integrate PrEP into clinical infrastructure rather than stand-alone research studies or demonstration projects.…”
Section: To the Editorssupporting
confidence: 62%
See 1 more Smart Citation
“…In a three site study in real-world clinical settings, 57% (98/171) of patients were retained in PrEP care at six months. 3 These findings were consistent across three diverse clinical settings in Jackson, Mississippi (61%; 37/61); Providence, Rhode Island (53%; 42/80); and Saint Louis, Missouri (63%; 19/30, p =0.51). However, our higher rates of retention in care reflect our efforts to integrate PrEP into clinical infrastructure rather than stand-alone research studies or demonstration projects.…”
Section: To the Editorssupporting
confidence: 62%
“…8 Furthermore, patients who remained in PrEP care had initially reported risk behaviors or being members of sexual networks that might place them at high risk for HIV acquisition; 89% of our patients were MSM and 69% reported condomless anal sex at least once in the last three months. 3 However, less is understood about the risk behaviors of patients who are not retained in care; it is conceivable that some individuals who are not retained may no longer need PrEP, and therefore discontinue PrEP care. On the other hand, it is conceivable that patients lost to follow-up are the most vulnerable and are at highest risk for HIV acquisition.…”
Section: To the Editorsmentioning
confidence: 99%
“…The study evaluated PrEP initiation defined as receiving a prescription; subsequent retention in care and adherence were beyond the scope of this analysis but are reported elsewhere. 31,32 Additionally, patients may have sought PrEP care elsewhere after the PrEP education session, which we were not able to measure or incorporate in our analysis. On the level of clinic operations, we lost a significant number of PrEP candidates during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…One study of PrEP utilization in clinics in 3 mid-sized U.S. cities found that retention in PrEP care was suboptimal, with only 57% of patients retained in PrEP care at 6 months after initiation. Among those patients retained in care at 6 months, the proportion of patients with optimal adherence for the prior month ranged from 33 to 77%, suggesting a need for interventions to support adherence in real-world clinical settings [70]. …”
Section: Emerging Challengesmentioning
confidence: 99%